The Norton Anthology of World Religions: Hinduism. Wendy Doniger (ed.). Series edited by Jack Miles. New York: W.W. Norton & Co, 2015. P.p.753 + xxxii. ISBN 978-0-393-91259-9. (2016) - Wood, Martin
No abstract available